The Effects of Potentiostat Scan Rate Variation on Impedance Value, Topography, and Morphology of the Polyaniline Thin Film - Iqomatus Sa'diyah; Nugrahani Primary Putri (Universitas Negeri Malang, 2021)
The effects of potentiostat scan rate on the impedance, topography, and morphology of the Polyaniline (PANi) thin film has observed in this study. PANi has deposited on the Quartz Crystal Microbalance (QCM) surface with various scan rates, and changes in the impedance value have observed through an impedance analyzer test. Topography Measurement System (TMS) has observed the layer topography, while the layer morphology has observed using optical microscopy and Scanning Electron Microscope (SEM). The results have shown that the best sample has a scan rate of 10 mV/s, with a low impedance value indicating the layer has rigid. The variation in scan rate can affect the impedance value, but it is not significant and does not indicate a damping effect on QCM. A homogeneous layer is deposited at a low scan rate from topography and morphological observations, while a high scan rate results in an inhomogeneous layer.DOI: 10.17977/um024v6i22021p046